Phylogeny and codivergence in the fig-fig wasp mutualism : sycoecine and agaondid fig wasps (Chalcidoidea, Hymenoptera) associated with Ficus section Galoglychia (Moraceae) - Underhill, Jenny G (Department of Biological Sciences, 2014)
Includes abstract.